Analisis Implementasi Kebijakan Wajib Belajar 12 Tahun Di Kabupaten Nunukan - Carlos Boby Janerio Lamar; Endang Poerwanti; Ichsan Anshory (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to describe: 1) Implementation of 12 years of compulsory education in Nunukan District, 2) obstacles faced and efforts made on the implementation of the compulsory 12-year study. The study was conducted in Nunukan District. Data collection techniques are interview, observation, and documentation. Analytical techniques used are data reduction, data exposure, and conclusions. To check the validity of data using technique triangulation and source. Research result; 1) Implementation of the 12 years compulsory education in Nunukan District proved to be done without the charge for the SPP at the level of elementary School, Junior School, high school / vocational school. APM fluctuates, the rate of continuing school reaches 92% upward, the passing rate reaches 99% and the dropout rate reaches 0.36%. 2) 12-year fair implementation constraints in Nunukan District are (a) individual mindset: (b) economic condition (c) lack of parental attention; (d) lack of facilities and infrastructure; (e) geographical location as transmigration area; (f) school distance; (g) lack of equity and teacher training; (h) early marriage. 3) Efforts made on the fair implementation of 12 years: (a) The government conducts persuasive socialization to the community for going to school; (b) School dropouts are advised to take non-formal education; (c) The government seeks to make equal distribution of teachers throughout the Nunukan Regency; (d) The procurement of facilities and infrastructure in the 3T area.Keywords: Implementation of policy, Compulsory Education, 12 years Abstrak: Penelitian ini bertujuan mendeskripsikan: 1) Implementasi wajib belajar 12 tahun di Kabupaten Nunukan, 2) kendala yang dihadapi dan upaya yang dilakukan pada implementasi wajib belajar 12 tahun. Jenis penelitian yang digunakan yaitu kualitatif deskriptif. Teknik pengumpulan data yaitu wawancara, observasi dan dokumentasi. Teknik analisis yang digunakan yaitu reduksi data, paparan data dan kesimpulan. Untuk mengecek keabsahan data menggunakan triangulasi teknik dan sumber. Hasil penelitian; 1) Implementasi wajib belajar 12 tahun di Kabupaten Nunukan terbukti terlaksana tanpa punggutan untuk SPP pada jenjang SD, SMP, SMA/SMK. APM mengalami fluktuatif, angka melanjutkan sekolah mencapai 92% ke atas, angka kelulusan mencapai 99% dan angka putus sekolah mencapai 0,36%. 2) Kendala implementasi wajar 12 tahun di Kabupaten Nunukan yaitu (a) mindset individu: (b) keadaan ekonomi (c) kurangnya perhatian orangtua; (d) kekurangan sarana dan prasarana; (e) letak geografis sebagai daerah transmigrasi; (f) jarak sekolah; (g) kurangnya pemerataan dan pelatihan guru; (h) nikah muda. 3) Upaya yang dilakukan pada implementasi wajar 12 tahun: (a) Pemerintah melakukan sosialisasi persuasif kepada masyarakat agar mau bersekolah; (b) Masyarakat yang putus sekolah disarankan untuk mengambil pendidikan non formal; (c) Pemerintah berupaya melakukan pemerataan guru ke seluruh wilayah Kabupaten Nunukan; (d) Pengadaan sarana dan prasarana di wilayah 3T.Kata Kunci: Implementasi kebijakan, Wajib belajar, 12 Tahun